2017
DOI: 10.1002/jeab.242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shifts in food reinforcement context on rats’ consumption of concurrently available water or sucrose solution

Abstract: The purpose of this study was to investigate the effects of signaled transitions from relatively rich to lean conditions of food reinforcement on drinking concurrently available water or sucrose-sweetened water in rats. Past research demonstrated that these negative incentive shifts produce behavioral disruption in the form of extended pausing on fixed-ratio schedules. Four male Long-Evans rats operated on a two-component multiple fixed-ratio fixed-ratio schedule. In one manipulation, the ratio was held consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 33 publications
7
9
0
Order By: Relevance
“…Consistent with general findings by Galuska and Sawyer (2017), extended pausing during the negative incentive shift was most robust with access to the sucrose solution. For each rat in each condition, the median (and IQR) pause duration and running response rate per transition were calculated and shown in Tables 1 and A1, respectively.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Consistent with general findings by Galuska and Sawyer (2017), extended pausing during the negative incentive shift was most robust with access to the sucrose solution. For each rat in each condition, the median (and IQR) pause duration and running response rate per transition were calculated and shown in Tables 1 and A1, respectively.…”
Section: Resultssupporting
confidence: 87%
“…Based on the procedure developed by Perone and Courtney (1992), Galuska and Sawyer arranged a multiple FR FR schedule. Galuska and Sawyer (2017) found that, consistent with past findings, the negative incentive shift produced behavioral disruption as indexed by extended pausing. Components were signaled by retractable levers, such that insertion of the left lever was correlated with the large magnitude reinforcer and insertion of the right signaled the small.…”
supporting
confidence: 89%
See 3 more Smart Citations